2021
DOI: 10.1177/13623613211057974
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive behaviour in autism: A scoping review

Abstract: The ability to deceive is a key milestone in social cognitive development for typically developing individuals. In this scoping review, we systematically searched the literature to summarise research on deceptive behaviour in autism and identify gaps in knowledge. Across the 28 studies identified, three main themes were synthesised, with seven subthemes: (1) Deception ability and prevalence (1a) gameplay deception; (1b) naturalistic deception; (2) Psychological correlates of deception (2a) verbal, intellectual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…We found that autistic mock-suspects displayed similar verbal deception cues (in terms of statement-evidence consistency and investigation-relevant information) to the non-autistic group regardless of whether they were telling the truth or being deceptive. To our knowledge this was the first study in which autistic adults (without co-occurring intellectual disability) actively demonstrated the ability to tell verbal lies (see Bagnall et al, 2022 ). Specifically, the degree to which mock-suspects lied through omitting incriminating actions during the VE task (therefore contradicting the incriminating evidence) was similar regardless of diagnostic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that autistic mock-suspects displayed similar verbal deception cues (in terms of statement-evidence consistency and investigation-relevant information) to the non-autistic group regardless of whether they were telling the truth or being deceptive. To our knowledge this was the first study in which autistic adults (without co-occurring intellectual disability) actively demonstrated the ability to tell verbal lies (see Bagnall et al, 2022 ). Specifically, the degree to which mock-suspects lied through omitting incriminating actions during the VE task (therefore contradicting the incriminating evidence) was similar regardless of diagnostic group.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the verbal behavior of autistic suspects who are actively deceptive is also crucial for effective investigative interviewing practice. While there is a substantial body of research showing that autistic children have difficulty with lying, relatively little is known about deception in autistic adulthood ( Bagnall et al, 2022 ). Over the past few years, there have, however, been high-profile criminal cases in the United Kingdom (UK) in which autistic defendants have deceived others (e.g., Murray, 2020 ; De Simone, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simply saying “I don't like this” might be the full truth, but in this situation it is an unnecessary one that could damage the relationship. A recent scoping review concluded that although autistic people can lie, they do so less adeptly than nonautistic people (Bagnall et al, 2022). This pattern of greater difficulty with expressive deception could be due to autistic people using different strategies to deceive, which are potentially informed by their use of different strategies used to detect deception.…”
Section: Relevance Of Deception Detection To the Autistic Communitymentioning
confidence: 99%
“…That is, when two minds meet, there is a disconnect: differences in cognitive styles and life experiences can make it difficult for social partners to empathize with one another and can contribute to misunderstandings and uncertainties in interactions (Milton, 2012). Because deception is an inherently social behavior (Bagnall et al, 2022), the presence of the DEP between autistic and nonautistic communicators (Milton, 2012) may also decrease deception detection. Importantly, given their status as a neurominority and the devaluation of autistic communication styles, the negative effects of the DEP—including being blamed for communication outcomes like being deceived—are likely to disproportionately affect autistic people (DeThorne, 2020).…”
Section: Relevance Of Deception Detection To the Autistic Communitymentioning
confidence: 99%
“…We also test two potential strengths, honesty (Bagnall et al, 2021) and loyalty (Russell et al, 2019), that are often mentioned for autistic individuals and as such we use an autism-focused word set of {"autism," "autistic," "asperger"} versus {"typical," "regular," "average"} for these two tests. Results are depicted in Table 3.…”
Section: Testmentioning
confidence: 99%